Online shopping: Factors that affect consumer purchasing behaviour - Jozef Bucko; Lukáš Kakalejčík; Martina Ferencová (Cogent Business & Management, 2018)
The objective of this paper is to determine factors that affect the consumers' willingness to purchase product from the online store. We evaluated the criteria based on which users make decisions when purchasing online. We conducted principal components analysis to reduce the number of these criteria and created seven factors. To confirm factors are accurate, we executed confirmatory factor analysis that proved that model consisting of the newly created factors fits the data well.
Keywords: 650